Effect of Site of Injection on Spread of Spinal Anaesthesia with Hyperbaric Bupivacaine (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
Ninety unpremeditated patients (20-40 years) undergoing caesarean section were allocated randomly to receive 0.5% hyperbaric bupivacaine 2ml at the site of L2-3, L3-4 and L4-5 intervertebral space. Spinal injection was performed to all patients with a 25-gauge Quincke spinal needle. The onset time of analgesia at T10 and T6 was significantly faster and the level of analgesia at 5 and 10 min was significantly higher after injection at L2-3. But the maximum height (T4) of analgesia at 15 and 20 min after injection and the number of episodes of hypotension were not significantly different among the three groups. Key words: Spinal anaesthesia, hyperbaric bupivacaine, site of injection, spread of anaesthesia.   Journal of BSA, Vol. 20, No. 2, July 2007 p.51-55